Materials to the Polish flora in the Herbarium of the University of Łódź. Part XIX. Adoxaceae, Alismataceae, Araceae, Aristolochiaceae, Asclepiadaceae, Balsaminaceae, Butomaceae, Gentianaceae, Hippuridaceae, Hydrocharitaceae, Lythraceae, Menyanthaceae, Scheuchzeriaceae - Fagasiewicz, Lucyna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2005)
The study contains the revision o f the herbarium specimens on the families Adoxaceae, Alismataceae, Araceae, Aristolochiaceae, Asclepiadaceae, Balsaminaceae, Butomaceae, Gentianaceae, Hippuridaceae, Hydrocharitaceae, Lythraceae, Menyanthaceae and Scheuchzeriaceae preserved in LOD. AU corrections of identifications are marked with the+.